N-acetyl-l-methionine is a superior protectant of human serum albumin against photo-oxidation and reactive oxygen species compared to N-acetyl-l-tryptophan - Kouno, Yousuke; Anraku, Makoto; Yamasaki, Keishi; Okayama, Yoshiro; Iohara, Daisuke; Ishima, Yu; Maruyama, Toru; Kragh-Hansen, Ulrich; Hirayama, Fumitoshi; Otagiri, Masaki (Biochimica et biophysica acta, 2014)
Sodium octanoate (Oct) and N-acetyl-l-tryptophan (N-AcTrp) are widely used as stabilizers during pasteurization and storage of albumin products. However, exposure to light photo-degrades N-AcTrp with the formation of potentially toxic compounds. Therefore, we have examined the usefulness of N-acetyl-l-methionine (N-AcMet) in comparison with N-AcTrp for long-term stability, including photo stability, of albumin products. Recombinant human serum albumin (rHSA) with and without additives was photo-irradiated for 4weeks. The capability of the different stabilizers to scavenge reactive oxygen species (ROS) was examined by ESR spectrometry. Carbonyl contents were assessed by a spectrophotometric method using fluoresceinamine and Western blotting, whereas the structure of rHSA was examined by SDS-PAGE, far-UV circular dichroism and differential scanning calorimetry. Binding was determined by ultrafiltration. N-AcMet was found to be a superior ROS scavenger both before and after photo-irradiation. The number of carbonyl groups formed was lowest in the presence of N-AcMet. According to SDS-PAGE, N-AcMet stabilizes the monomeric form of rHSA, whereas N-AcTrp induces degradation of rHSA during photo-irradiation. The decrease in α-helical content of rHSA was the smallest in the presence of Oct, without or with N-AcMet. Photo-irradiation did not affect the denaturation temperature or calorimetric enthalpy of rHSA, when N-AcMet was present. The weakly bound N-AcMet is a superior protectant of albumin, because it is a better ROS-protector and structural stabilizer than N-AcTrp, and it is probable and also useful for other protein preparations. N-AcMet is an effective stabilizer of albumin during photo-irradiation, while N-Ac-Trp promotes photo-oxidative damage to albumin. [Display omitted] •N-acetyl-l-methionine can replace N-acetyl-l-tryptophan for albumin products.•N-acetyl-l-methionine acts as a new and safe stabilizer for albumin products.•N-acetyl-l-tryptophan has low photo-stability and could give rise to toxic compounds.•N-acetyl-l-methionine was found to be a superior ROS scavenger.•N-acetyl-l-tryptophan induces degradation of albumin during photo-irradiation.